Transportation Efficiency Based On Empowerment Of Private And Government Businesses With The Concept Of Collaboration - Amrullah, Romanda Annas; Moejiono; Nofandi, Faris; Santoso, Agus Dwi; Arleiny; Pratama, Rizki Adi (Meteor STIP Marunda, 2024)
The disproportionate growth between the transportation fleet and the infrastructure causes congestion, pollution, inconvenience and poor service. However, the high growth in transportation fleets managed by the private sector more than those managed by the government is not effective, on the other hand the government does not have enough funds to provide adequate public transportation facilities, so the concept of Allocation Cheap Sourcing is needed which is a collaboration between fleets managed by the private sector and the government. The method used in this study is Evidence based policy . The results of the study show that the effectiveness of collaboration can be in the form of partnerships and new forms of organization (NFO).